Consequences of Trace Element Deficiency (Copper, Cobalt, Iodine, and Selenium) in Ruminants - Jalalzai, Fazalwali; Sangary, Mohammad (Journal of Natural Sciences – Kabul University, 2025)
For the numerous cells of the body to perform their functions normally, it is essential to ensure an adequate supply of minerals in the animal's diet. This study aims to examine the symptoms and consequences of a deficiency of essential minerals, including copper, cobalt, iodine, and selenium, in ruminant animals. The study is conducted through a review method based on reliable scientific sources. The findings of this review show that a deficiency of essential minerals can be caused by soil depletion, imbalanced nutrition, and metabolic disorders. The reduction of these elements leads to abnormalities such as a weakened immune system, reproductive disorders, growth retardation, and skin problems in animals. The conclusion of this research suggests that accurately identifying the factors leading to the depletion of these minerals and preventing their depletion plays a key role in maintaining the health and productivity of ruminants.